Analysis of the Content of the English Textbook "Bright 1" for Grade VII Junior High School/MTs Students Based on Alan Cunningswort's Theory - Lestari, Indah; Qalyubi, Imam; Normuliati, Sri (Journal of English Language and Education, 2025)
This study uses English textbooks as the object of study. The purpose of this study is to determine the extent to which the contents of the English textbook "BRIGHT" for junior high school students meet the criteria based on Alan Cunningsworth. This study uses a qualitative approach with a data presentation analysis method, which compares the number of criteria met with the total number of EFL (English as a Foreign Language) evaluation criteria. The percentage of criteria met is calculated by dividing the number of criteria met by the total criteria, then multiplied by 100%. The results of the study indicate that the English textbook "BRIGHT" for grade VII junior high school meets various criteria, with the following details: the criteria for objectives and approaches obtained 90.62%, language content 90%, skills 89.70%, topics 90.52%, methodology 94.57%, teacher's book 0%, and practical considerations 100%. The average total score of the criteria met is 79.34%. This shows that the textbook "BRIGHT 1" is good enough to be used as a learning resource for students.